Ambiguities of PGPR-Induced Plant Signaling and Stress Management - Jalmi, Siddhi Kashinath; Sinha, Alok Krishna (Frontiers in Microbiology, 2022)
The growth and stress response developed by the plant in virtue of the action of PGPR is dictated by the changes in hormone levels and related signaling pathways. Each plant possesses its specific type of microbiota that is shaped by the composition of root exudates and the signal molecules produced by the plant and microbes. Plants convey signals through the diverse and complex signaling pathways. The signaling pathways are also controlled by phytohormones wherein they regulate and coordinate various defense responses and developmental stages. On account of improved growth and stress tolerance provided by the PGPR to plants, there exist a crosstalk of signaling events between phytohormones and other signaling molecules secreted by the plants and the PGPR. This review discusses some of the important aspects related to the ambiguities of signaling events occurring in plants, allowing the interaction of PGPR with plants and providing stress tolerance to the plant.